Berkas-berkas Sukarno, 1965-1967 : kronologi suatu keruntuhan - Dake, A. C. A. (Antonie C. A.), 1928- (Jakarta : Aksara Karunia, 2005)
Chronological documents on the fall of Sukarno and the 1965 Coup in Indonesia
Daftar Pustaka : p. 523-532 and index
Keywords: Soekarno, -- 1901-1970; Indonesia -- History -- Coup d'etat, -- 1965; Indonesia -- Politics and government -- 1950-1966